Wave energy resource assessment for the Indian shelf seas. (April 2015) - Sanil Kumar, V.; Anoop, T.R.
Abstract: As a renewable energy, the assessment of wave power potential around a country is crucial. Knowledge of the temporal and spatial variations of wave energy is required for locating a wave power plant. This study investigates the variations in wave power at 19 locations covering the Indian shelf seas using the ERA-Interim dataset produced by the European Centre for Medium-Range Weather Forecasts (ECMWF). The ERA-Interim data is compared with the measured wave parameters in the Arabian Sea and the Bay of Bengal. Along the western shelf seas of India, the seasonal oscillations lead to variation of the wave power from the lowest seasonal mean value (2.6 kW/m) in the post-monsoon period (October–January) to the highest value (25.9 kW/m) in the south-west monsoon (June–September) period. Significant (10–20%) inter-annual variations are detected at few locations. The mean annual wave power along the eastern Indian shelf seas (2.6–9.9 kW/m) is lower than the mean annual wave power along the western part (7.9–11.3 kW/m). The total annual mean wave power available along the western shelf seas of India is around 19.5 GW. Along the eastern shelf seas, it is around 8.7 GW. In the Indian Shelf seas, the annual mean wave power is highest (11.3 kW/m) at the southern location (location 11), and the seasonal variation in wave power is also less. Hence, location 11 is a better location for a wave power plant in the Indian shelf seas. Highlights: Studied wave power at 19 locations along Indian shelf seas over a 34-year period. Mean annual wave power along western shelf seas is higher than eastern shelf seas. At southern location, highest wave power with less seasonal variations is found. Significant (10–20%) inter-annual variations are detected at a few locations.